Beneficial role of acetylcholine in chlorophyll metabolism and photosynthetic gas exchange in Nicotiana benthamiana seedlings under salinity stress. (12th January 2020) - Qin, C.; Ahanger, M. A.; Zhou, J.; Ahmed, N.; Wei, C.; Yuan, S.; Ashraf, M.; Zhang, L.
Abstract: Acetylcholine (ACh) is believed to improve plant growth. However, regulation at biochemical and molecular levels is largely unknown. The present study investigated the impact of exogenously applied ACh (10 µm ) on growth and chlorophyll metabolism in hydroponically grown Nicotiana benthamiana under salt stress (150 mm NaCl). Salinity reduced root hydraulic conductivity while ACh‐treated seedlings exhibited a significant increase, resulting in increased relative water content. Salinity induced a reduction in chlorophyll biosynthetic intermediates, such as protoporphyrin‐IX, Mg‐photoporphyrin‐IX and protochlorophyllide, which were significantly ameliorated in the presence of ACh. This influence of ACh on chlorophyll synthesis was confirmed by up‐regulation of HEMA1, CHLH, CAO and POR genes. Gas exchange parameters, i.e. stomatal conductance, internal CO2 concentration and transpiration rate, increased with ACh, thereby alleviating the salinity effects on photosynthesis. In addition, the salinity‐induced enhancement of lipid peroxidation declined after ACh treatment through modulation of the activity of the assayed antioxidant enzymes (superoxide dismutase and peroxidase). Importantly, ACh significantly reduced the uptake of Na and increased uptake of K, resulting in a decline in the Na/K ratio. Results of the present study indicate that ACh can be effective in ameliorating NaCl‐induced osmotic stress, altering chlorophyll metabolism and thus photosynthesis by maintaining ion homeostasis, hydraulic conductivity and water balance. Abstract : Acetylcholine increases tolerance to salt stress in Nicotiana benthamiana .